Dark carousel [compact disc, unabridged] - Feehan, Christine (Feehan, Christine. Dark series., 2016)
The moment Charlotte Vintage walks into his club, Tariq Asenguard's blood is set on fire. The ancient Carpathian had given up hope of finding his lifemate, but now he will do anything to make Charlotte his own. What Tariq doesn't know is that Charlotte is using herself and her best friend as bait, to try to draw out the bloodthirsty killers who have already murdered Charlotte's brother and mentor.